Examining Configurations and Firm Performance in a Suboptimal Equifinality Context - Payne, G. Tyge (Organization Science, 2006)
Gresov and Drazin’s (1997) suggestions regarding the study of equifinality are used to investigate the organizational configurations that exists within a suboptimal equifinality context. A suboptimal equifinality situation exists when organizations must satisfy multiple and conflicting functional demands with a restricted set of design options; these restrictions force all organizations to operate suboptimally. Gresov and Drazin (1997) speculate that in such a situation legitimacy claims are made about one function being more important than the other(s) so that an increased quantity of acceptable organizational forms are established. Additionally, they argue that a misfit penalty is likely to exist for organizations that deviate from the preferred configurational design. With data from the medical group industry, these speculations about suboptimal equifinality situations are tested using multivariate regression analyses. Findings show that the configuration type aligning with the preferred functional demand of quality performs relatively higher than those aligning with operational efficiency or attempting to meet both demands. Additionally, the greater the organization’s deviation from that design, the lower the financial performance. In summary, this study demonstrates that it is useful to take a functional equivalence perspective when examining variance in firm performance that is caused by design differences. Such an approach allows a more complete understanding of the fit-performance relationship by explicitly considering three factors: (i) the number of and level of conflict(s) among functional demands placed on the organization, (ii) the structural design options available to the decision maker, and (iii) the trade-offs that exist.